2023
DOI: 10.1097/js9.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary neoplasms of the bile duct: a European retrospective multicenter observational study (EUR-IPNB study)

Abstract: Background/Purpose: Intraductal papillary neoplasm of the bile duct (IPNB) is a rare disease in Western countries. The main aim of this study was to characterize current surgical strategies and outcomes in the mainly European participating centers. Methods: A multi-institutional retrospective series of patients with a diagnosis of IPNB undergoing surgery between 1 January 2010 and 31 December 2020 was gathered under the auspices of the European-African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this case, the exact location of tumor extension could not be determined by contrast-enhanced CT alone, and POCS was performed to determine that the tumor extended to the lower common bile duct. An analysis of patients who underwent surgery for IPNB reported a significantly lower overall survival for patients with extrahepatic extension of the tumor compared to those with intrahepatic localization of the tumor, suggesting that POCS plays an essential role in preoperative diagnosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the exact location of tumor extension could not be determined by contrast-enhanced CT alone, and POCS was performed to determine that the tumor extended to the lower common bile duct. An analysis of patients who underwent surgery for IPNB reported a significantly lower overall survival for patients with extrahepatic extension of the tumor compared to those with intrahepatic localization of the tumor, suggesting that POCS plays an essential role in preoperative diagnosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent European multicenter study showed a median postoperative survival of 5.7 years and a 5-year overall survival of 63%[ 17 ]. In unfit patients, novel endoscopic resection[ 1 ], endoscopic radiofrequency ablation or photodynamic therapy can be performed[ 8 ].…”
Section: To the Editormentioning
confidence: 99%
“…We read the article by Lluís et al . 1 recently published in the International Journal of Surgery with great interest and pleasure. This study comprised the largest number of centers and patients to date in Europe for a study providing surgical strategies and outcomes of intraductal papillary neoplasm of the bile duct (IPNB) and is the first to apply textbook outcome (TO) as a prognostic factor in patients with IPNB.…”
mentioning
confidence: 99%